Character displacement in the midst of background evolution in island populations of Anolis lizards: A spatiotemporal perspective. (1st October 2020) - Kamath, Ambika; Herrmann, Nicholas C.; Gotanda, Kiyoko M.; Shim, Kum C.; LaFond, Jacob; Cottone, Gannon; Falkner, Heather; Campbell, Todd S.; Stuart, Yoel E.
Abstract: Negative interactions between species can generate divergent selection that causes character displacement. However, other processes cause similar divergence. We use spatial and temporal replication across island populations of Anolis lizards to assess the importance of negative interactions in driving trait shifts. Previous work showed that the establishment of Anolis sagrei on islands drove resident Anolis carolinensis to perch higher and evolve larger toepads. To further test the interaction's causality and predictability, we resurveyed a subset of islands nine years later. Anolis sagrei had established on one island between surveys. We found that A. carolinensis on this island now perch higher and have larger toepads. However, toepad morphology change on this island was not distinct from shifts on six other islands whose Anolis community composition had not changed. Thus, the presence of A. sagrei only partly explains A. carolinensis trait variation across space and time. We also found that A. carolinensis on islands with previously established A. sagrei now perch higher than a decade ago, and that current A. carolinensis perch height is correlated with A. sagrei density. Our results suggest that character displacement likely interacts with other evolutionary processes in this system, and that temporal data are key to detecting such interactions.